add the equations.
Now for a, by elimination
multipy the second equation by -2
add now the first and this equation, giving
Math! - 6a + 5b = 10 , 6a - b = -110 a=________ b=_________ 6a + 5b = 10 6a - b...
algebra - Given g(x) = –2x – 1, find g(3a). G(3a)=-2(3a)-1 = -6a-1 = -5 is this ...
Am I doing Algerba right? - 6a for a = 3 and a = -4 So is it A. 6a = 6*3 = 18? B...
math - solve by substitution: a-1.2b=-3 0.2b+0.6a=12
Algebra - (9a^3b^4-12a^2b^5+6ab^7)/(6a^2b^3)
Math - Use the method of substitution to solve the linear equation! 6a=6-b 6a=5-...
algebra - Is this correct? subtract (4a^3+2b^3)-(6a^3+5a^2b-2ab^2+2b^3) answer...
Algebra - (3a^2+6ab-a-2b)/(9a^2-6a+1)
Math - 6a(3a-2) + 12b(3a-2) Is it correct if i multiplied 6a by 3a then 6a by -2...
math - 3a^2b + 6a^2b 9a^4b^2